An Analytical Study of Augmented and Virtual Reality in Online Learning: Exploring Technological Advancements and Pedagogical Impacts - MITHUN RAMAKRISHNAPPA; Archana MANJEGOWDA; Maltesh Shripadrao KULKARNI; Varsha Tindlu RAJGOPAL (RADINKA JAYA UTAMA PUBLISHER, PADANG< INDONESIA, 2025)
This research presents an analytical study on the integration of Augmented Reality (AR) and Virtual Reality (VR) in online learning, focusing on recent technological advances and their pedagogical implications. The study explores how immersive technologies transform digital education by enhancing student engagement, conceptual understanding, and experiential learning. Utilizing a descriptive quantitative research design, data were collected through a targeted survey of 12 participants, including students and educators experienced in AR and VR environments. The findings indicate that while awareness and adoption of AR and VR are increasing, a significant portion of learners remains unfamiliar with these tools or lacks access due to high costs and infrastructure barriers. Nevertheless, a majority of respondents reached a consensus that AR and VR significantly improves engagement and comprehension compared to traditional online instruction. The study identifies key technological enablers such as affordable hardware, mobile accessibility, AI integration, and cloud computing that have facilitated broader adoption. However, challenges persist, particularly regarding limited access to high-end devices and a lack of longitudinal empirical research on long-term learning efficacy. The study concludes that AR and VR possesss the power to transform online education, provided that institutions prioritize investments in faculty training, specialized content development, and inclusive access strategies.